Plan de negocio para una productora y comercializadora de productos cárnicos congelados en la línea de chuletas (2015)
Our graduate thesis “A business plan to produce and commercialize frozen breaded meats without preservatives. “This project was conducted on behalf of a descriptive exploratory study. This project permitted the identification and characteristics of the future buyers. In addition to determining the following requirements needed for this business in the municipal of Armenia, this business plan gathered its information from these following industries; technical, social economic, environmental, organizational and financial. Leading up to the development, these three methods were implemented(observation,deduction,and induction) which completed the formalization and positioning in the following market of producing and commercializing frozen breaded meats”Chuletas Max” in Armenia.